Gamification in education: problems of application and development prospects - Жакупова, Алтынай; Еркебаева, Сауле; Каримова, Разия; Тезел Шахин, Фатма (Pedagogy and Psychology, 2022)
At the present time, information and digital work is very relevant for the development of the educational sphere. In this article, the concept of gamification is considered as one of the directions of information and civil technologies in the education. Gamification is considered as a method of effective learning, to increase cognitive activity, to encourage, using elements of game design. It based on the research work of various scientists, they gave a description of the concept of gamification. The purpose of the article is to help future teachers of pre-school educational institutions in their professional activities to determine the level of preparedness of organizational actions of pre-school children using elements of gemifications. To achieve the purpose of the study, the following tasks were set: analysis of the concept of "gamification in education" and definition of the concept; conduct a survey to determine the advantages of gamification and data analysis; identify the main components of the gamification competencies of future pre-school teachers. The research methodology consists of analyses based on the method of content analysis of data obtained as a result of scientific research to determine "problems and prospects for the development of gamification in education." The scientific and practical significance of determining the effectiveness of gamification used in the upbringing and training of pre-schoolers: professional knowledge and (cognitive) skills in the gamification of education, as well as the definition of such components of training as methodological and organizational, information and communication and value-motivational relationships. The value of the research work: the analysis of the content presented in the article allowed us to describe the features of gamification in education, to determine the advantage of using gamification through a qualitative research method of case-study design, to form a development perspective. As a result of the study, the use of gamification elements forms the skills of an individual to effectively use digital educational resources: considering a way to easily solve complex problems, the possibility of using mobile service applications and creating a mobile gaming application with educational content will give good results. This article was prepared in accordance with the agreement of KazNPU named after Abay No. 3 of 2022.